2017
DOI: 10.1155/2017/3804356
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Bioactive Constituents and Analgesic Effects of MyrLiq®, a Commiphora myrrha Extract with a High Furanodiene Content

Abstract: The analgesic properties of myrrh (Commiphora myrrha) have been known since ancient times and depend on the presence of bioactive sesquiterpenes with furanodiene skeletons. MyrLiq is a C. myrrha extract with a standardized content of curzerene, furanoeudesma-1,3-diene, and lindestrene (12.31 ± 0.05 g kg−1, 18.84 ± 0.02 g kg−1, and 6.23 ± 0.01 g kg−1, resp.) and a high total furanodiene content (40.86 ± 0.78 g kg−1). A balanced sample of 95 female and 89 male volunteers (with ages ranging from 18 to older than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…For the female group, the extract was effective against low back pain and fever-dependent pain at the doses of 200 mg/day. Furthermore, no side effect was reported by any of the volunteers (Germano et al, 2017). Overall the clinical evidence is High for pain associated with fever.…”
Section: Commiphora Molmolmentioning
confidence: 69%
“…For the female group, the extract was effective against low back pain and fever-dependent pain at the doses of 200 mg/day. Furthermore, no side effect was reported by any of the volunteers (Germano et al, 2017). Overall the clinical evidence is High for pain associated with fever.…”
Section: Commiphora Molmolmentioning
confidence: 69%
“…Compared with the best known painkillers, it showed similar effects, although it required a longer course of treatment (about 20 days); however, none of the volunteers reported undesirable side effects or toxicity on the liver and kidneys with doses up to 11.5 mg/kg of body weight per day for 8-12 weeks of treatment. 37 Analgesic properties have been attributed to the presence in myrrh resin of bioactive sesquiterpenes with furanodiene structures: furanoeudesma-1,3-diene, lindestrene, and curzerene, which are responsible for the aroma and high analgesic activity of myrrh.…”
Section: Phytotherapy and Headachementioning
confidence: 99%
“…A study by Langhorst et al confirms the safety and tolerability of the long term use of Myrrh (1200 mg/day) plus chamomile extract (840 mg/day) and coffee charcoal (600 mg/day) in patients with ulcerative colitis [45]. No serious side effects were reported in previous trials using myrrh on human subjects [40,41]. However, a toxicological evaluation of Myrrh essential oil was conducted in mice and it was seen that lower doses of myrrh (1, 5, and 10 μL) did not cause skin inflammation, swelling, dermatitis, scabbing, and abrasions.…”
Section: Discussionmentioning
confidence: 82%
“…This herb was well tolerated and caused less adverse reactions compared to praziquantel. The analgesic effect of Myrrh has been studied in 184 patients in Italy [41]. The authors indicated that pain scores significantly decreased in male participants in the study after administration of 400 mg/day of Myrrh for 20 days, whereas, the alleviation of lower back pain and fever-dependent pain was brought about by only 200 mg/day of Myrrh in the female population [41].…”
Section: Discussionmentioning
confidence: 99%